Perancangan Aplikasi Animasi Interaktif Sosialisasi Kanker Payudara untuk Wanita Remaja dan Dewasa - Kuryanti, Sandra Jamu (Sinkron : jurnal dan penelitian teknik informatika, 2017)
There are types of cancer that many suffered and feared by women, namely breast cancer after cervical cancer. Breast cancer is a type of cancer that attacks the breast organ, where the cells in the breast divide and grow out of control. Breast cancer patients ranks first with the percentage of cases 43.1% and death percentage 12.9% (Data Globocan 2012). Signs of breast cancer today do not recognize the age limit, many cases found early signs of breast cancer in adolescence and cases of self-examination delay in Indonesia is very high reached more than 80%, so that found in advanced patients who can aggravate the situation. In response to this case, the authors are motivated to create an interactive animation application as a medium of socialization to the community, especially women so that they are aware of the importance of early detection of breast cancer and as prevention of breast cancer spread to a higher stage of lenih high.